Leadership development programmes perceived as important by Malaysian primary deputy principals: do demographic factors matter? / Lokman Mohd Tahir ... [et al.] - Mohd Tahir, Lokman; Abdul Aziz, Norazah; Ali, Mohd Fadzli; Yasin, M.Al-Muzammil; Hamzah, Lina Mursyidah; Hasnor, Hanin Naziha (Universiti Teknologi MARA, 2023)
The main purpose of this study was to examine a less explored and under-studied topic of professional development programmes deputy principals in Malaysian primary schools’ view as important. A survey was conducted using a self-developed questionnaire consisting of 18 items. The was distributed to deputy principals from all primary schools in the state of Johor and garnered a total of 318 responses. Descriptive and inferential statistical analyses were employed to obtain the means scores, whilst the t-test and one-way ANOVA were employed to measure the differences between deputy principals based on their demographic factors. The results revealed a number of professional development programmes deputy principals considered as beneficial to their leadership journey. Programmes such as financial management, school law, managing teachers’ competencies and teamworking were perceived as noteworthy and valuable and were believed to be capable of supporting deputy principals’ school management and leadership knowledge and skills. A significant difference between the deputy principals’ positions and their selection of professional development programmes was identified, while other demographic factors such as gender and years spent as a school leader were less significant.